2003
DOI: 10.1097/00126334-200312010-00010
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Partnerships Among Rural African Americans With Recently Reported Heterosexually Transmitted HIV Infection

Abstract: Concurrent partnerships likely accelerate heterosexual HIV transmission among blacks in the rural southeastern United States. Future research should examine the socioeconomic context that supports this network pattern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
109
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(120 citation statements)
references
References 24 publications
9
109
2
Order By: Relevance
“…In this study, several risk behaviors found to be associated with criminal justice involvement in previous cross-sectional research, such as multiple partnerships, 7,45,46 were not found to be temporally associated with arrest or incarceration. The findings of this paper do not necessarily contradict these studies; rather, they suggest that previously found associations may be spurious and are likely influenced by social and structural factors which impact upon both criminal justice involvement and sexual risk.…”
Section: Discussionmentioning
confidence: 42%
“…In this study, several risk behaviors found to be associated with criminal justice involvement in previous cross-sectional research, such as multiple partnerships, 7,45,46 were not found to be temporally associated with arrest or incarceration. The findings of this paper do not necessarily contradict these studies; rather, they suggest that previously found associations may be spurious and are likely influenced by social and structural factors which impact upon both criminal justice involvement and sexual risk.…”
Section: Discussionmentioning
confidence: 42%
“…12,13 After the incarceration, absence of a stable sex partner with stress of reintegration 66 may lead newly released prisoners to engage in increased levels of multiple and concurrent partnerships. 9,[15][16][17][18][19] A number of important study limitations should be noted. First, since this study was cross-sectional, we do not know the temporal relationship between incarceration and sexual risk behavior and hence cannot conclude that incarceration contributed to high-risk sex partnerships.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13][14] The absence of a stable partner, together with the stress of reintegration after incarceration, may lead newly released prisoners to engage in increased levels of multiple partnerships, including concurrent partnerships (multiple partnerships that overlap in time). 9,[15][16][17][18][19] Partnership concurrency is considered to be a particularly important determinant of STI/HIV transmission. 20 There is evidence that incarceration history is associated with high-risk sex partnerships including multiple and concurrent partnerships; 15,17,[21][22][23][24][25] however, most studies have been performed in small convenience samples.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 In addition to these risk factors, the characteristics of sexual networks among heterosexuals, 5 specifically the pattern of sex partner concurrency (overlapping sex partnerships in the same time interval), may help to explain the heterosexual spread of HIV and other STDs in sub-Saharan Africa [6][7][8] and in high-risk urban and rural areas in the United States. [9][10][11] A high prevalence of sex partner concurrency in a population has been hypothesized to increase the number of direct or indirect sexual connections and thereby to influence the extent, rapidity, and persistence of HIV and other STD epidemics. 12 However, the theory that sex partner concurrency is a driver of heterosexual HIV epidemics has been criticized for being based on limited evidence.…”
Section: Introductionmentioning
confidence: 99%